2018
DOI: 10.3390/nu10121944
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Plasma Docosahexaenoic Acid Levels and Their Relationship to Neurological and Cognitive Functions in PKU Patients: A Double Blind Randomized Supplementation Study

Abstract: Children with phenylketonuria (PKU) follow a protein restricted diet with negligible amounts of docosahexaenoic acid (DHA). Low DHA intakes might explain subtle neurological deficits in PKU. We studied whether a DHA supply modified plasma DHA and neurological and intellectual functioning in PKU. In a double-blind multicentric trial, 109 PKU patients were randomized to DHA doses from 0 to 7 mg/kg&day for six months. Before and after supplementation, we determined plasma fatty acid concentrations, latencies of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 65 publications
4
38
0
Order By: Relevance
“…Of the 33 studies included in this review, 13 studies had no reported blood fatty acid concentrations [ 29 , 31 , 33 , 35 , 36 , 38 , 43 , 44 , 45 , 49 , 52 , 53 , 55 ]. In 20 studies, fatty acid concentrations were reported, and the fatty acid concentrations were analyzed in a variety of bodily tissues and blood fractions (note that in some studies multiple fractions were utilized): plasma fatty acids [ 27 , 32 , 33 , 56 ], phospholipids in erythrocyte membranes [ 28 , 41 ], plasma phosphatidylcholine [ 30 ], erythrocyte phosphatidylcholine [ 30 ], erythrocyte phosphatidylethanolamine [ 30 ], cheek cells [ 37 , 48 ], capillary whole blood [ 40 , 46 , 47 , 50 ], serum phospholipids [ 42 , 57 , 58 ], total fatty acids in erythrocyte membrane [ 39 , 56 , 59 ], glycerol-phospholipids in plasma [ 51 ] and erythrocytes [ 54 ]. Unfortunately, recalculation formulae to the O3I equivalence are only available for a limited number of blood fractions [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 33 studies included in this review, 13 studies had no reported blood fatty acid concentrations [ 29 , 31 , 33 , 35 , 36 , 38 , 43 , 44 , 45 , 49 , 52 , 53 , 55 ]. In 20 studies, fatty acid concentrations were reported, and the fatty acid concentrations were analyzed in a variety of bodily tissues and blood fractions (note that in some studies multiple fractions were utilized): plasma fatty acids [ 27 , 32 , 33 , 56 ], phospholipids in erythrocyte membranes [ 28 , 41 ], plasma phosphatidylcholine [ 30 ], erythrocyte phosphatidylcholine [ 30 ], erythrocyte phosphatidylethanolamine [ 30 ], cheek cells [ 37 , 48 ], capillary whole blood [ 40 , 46 , 47 , 50 ], serum phospholipids [ 42 , 57 , 58 ], total fatty acids in erythrocyte membrane [ 39 , 56 , 59 ], glycerol-phospholipids in plasma [ 51 ] and erythrocytes [ 54 ]. Unfortunately, recalculation formulae to the O3I equivalence are only available for a limited number of blood fractions [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, recalculation formulae to the O3I equivalence are only available for a limited number of blood fractions [ 60 ]. The recalculation to the O3I equivalence was thus not possible for seven studies because they used a blood fraction for which no recalculation formula is available: erythrocyte and plasma phosphatidylcholine [ 30 ], erythrocyte phosphatidylethanolamine [ 30 ], cheek cells [ 37 ], serum phospholipids [ 42 ], cheek cells [ 48 ], glycerol-phospholipids in plasma [ 51 ] or serum phospholipids [ 57 , 58 ]. Moreover, in three studies only DHA levels were reported and recalculation to the O3I equivalence was thus not possible [ 39 , 40 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four articles were excluded after revision of the abstract. Of the 33 articles considered for evaluation of the complete text, nine articles were ultimately included in the systematic review [27,28,29,30,31,32,33,34,35].…”
Section: Resultsmentioning
confidence: 99%
“…The combined study population of the nine clinical trials included in this review was 419 individuals, 365 (87.1%) of whom had phenylketonuria. Only two studies included a healthy control group [29,33] and the remaining seven, a PKU control group [27,28,30,31,32,34,35]. Ages ranged from 2.1 weeks to 47 years.…”
Section: Resultsmentioning
confidence: 99%